AN ANALYSIS OF TRANSLATION PROCEDURES OF MEDICAL TERMS IN A MEDICAL TEXTBOOK ENTITLED "INTRODUCTION TO HUMAN PHYSIOLOGY" BY LAURALEE SHERWOOD - Eristianingrum, Ysahi Tantias (2014)
This study analyzed translation procedures of medical terms in a medical textbook entitled "Introduction to Human Physiology" by Lauralee Sherwood. The specific purposes of this study were to find out noun phrase structures in medical terms, translation procedures used in translating medical terms in noun phrase structures, and the appropriateness of medical terms translation in this medical textbook. This research employed a qualitative case study in which several steps were conducted. First, all medical terms were collected and categorized into noun phrase structures. Second, the translation of medical terms in noun phrase structures was analyzed in terms of its translation procedures by using Newmark's theory. Third, the appropriateness of medical terms translation was obtained by questionnaire and interview. The first result showed that there were 18 types of noun phrase structures appeared in 500 medical terms. Out of 18 types of noun phrase structures, there were four dominant noun phrase structures appeared namely 168 items of Noun (33,6%), 92 items of Adjective+Noun (18,4%), 74 items of Noun+Noun (14,8%), and 66 items of Adjective Phrase+Noun (13,2%). The second result showed that there were only seven translation procedures used in translating medical terms in noun phrase structures namely Couplet, Triplet, Naturalization, Transposition, Transference, Literal, and Quadruplet. Out of seven procedures, there were four most dominant translation procedures used in translating medical terms in noun phrase structures namely Couplet (46,4%), Triplet (19,4%), Naturalization (17,8%), and Transposition (7,6%). Moreover, the third result showed that the quality of medical terms translation was "Excellent" and the medical terms translation was appropriate to the target readers. It can be concluded that the medical terms in this medical textbook were well structured. The translator of this medical textbook applied the appropriate translation procedures in translating medical terms in noun phrase structures from source language into the target language. The appropriate use of translation procedures in translating medical terms in noun phrase structures led to the excellent quality of medical terms translation in which the medical terms translation was appropriate and acceptable to the target readers. It also indicated that the translator of "Introduction to Human Physiology" medical textbook succeeded transferring the meaning of terms from source language (SL) into target language (TL) accurately, clearly, and naturally because he tended to avoid using Literal in order not to produce doubtful translation. Keywords: translation, analysis, medical terms, noun phrase structures, translation procedures, appropriateness of translation. Penelitian ini menganalisis prosedur penerjemahan istilah medis dalam buku teks kedokteran yang berjudul "Pengantar Fisiologi Manusia" oleh Lauralee Sherwood. Tujuan khusus dari penelitian ini adalah untuk mengetahui struktur frasa nomina dalam istilah medis, prosedur penerjemahan yang digunakan dalam menerjemahkan istilah medis dalam struktur frasa nomina, dan ketepatan terjemahan istilah medis dalam buku medis ini. Penelitian ini menggunakan studi kasus kualitatif di mana beberapa langkah dilakukan. Pertama, semua istilah medis dikumpulkan dan dikelompokkan ke dalam struktur frasa nomina. Kedua, penjabaran istilah medis dalam struktur frasa nomina dianalisis dalam hal prosedur terjemahannya dengan menggunakan teori Newmark. Ketiga, kesesuaian penerjemahan istilah medis diperoleh dengan kuesioner dan wawancara. Hasil pertama menunjukkan bahwa ada 18 jenis struktur frasa nomina muncul di 500 istilah medis. Dari 18 jenis struktur frase nomina, ada empat struktur frasa nomina yang dominan muncul yaitu 168 item Noun (33,6%), 92 item Adjective+Noun (18,4%), 74 item dari Noun+Noun (14 , 8%), dan 66 item Adjective+Noun (13,2%). Hasil kedua menunjukkan bahwa hanya ada tujuh prosedur penerjemahan yang digunakan dalam menerjemahkan istilah medis dalam struktur frasa nomina yaitu Kuplet, Triplet, Naturalisasi, Transposisi, Transferensi, Literal, dan Kuadruplet. Dari tujuh prosedur, ada empat prosedur penerjemahan yang paling dominan digunakan dalam menerjemahkan istilah medis dalam struktur frasa nomina yaitu Kuplet (46,4%), Triplet (19,4%), Naturalisasi (17,8%), dan Transposisi (7,6%). Selain itu, hasil ketiga menunjukkan bahwa kualitas terjemahan istilah medis adalah "Sangat Baik" dan terjemahan istilah medis adalah tepat untuk target pembaca. Dengan demikian dapat disimpulkan bahwa istilah medis dalam buku medis ini adalah terstruktur dengan baik. Penerjemah buku medis ini menerapkan prosedur penerjemahan yang tepat dalam menerjemahkan istilah medis dalam struktur frasa nomina dari bahasa sumber ke dalam bahasa sasaran. Penggunaan yang tepat dari prosedur penerjemahan dalam menerjemahkan istilah medis dalam struktur frasa nomina menyebabkan kualitas terjemahan istilah medis sangat baik di mana terjemahan istilah medis yang tepat dan dapat diterima oleh target pembaca. Hal ini juga menunjukkan bahwa penerjemah buku medis "Pengantar Fisiologi Manusia" berhasil mentransfer makna istilah dari bahasa sumber (SL) ke bahasa sasaran (TL) secara akurat, jelas, dan secara alami karena ia cenderung menghindari menggunakan Literal agar tidak menghasilkan terjemahan yang diragukan.